The effect of mandala therapy on anxiety, pain severity and distress of primary dysmenorrhea: A randomized clinical trial - Mahsa Hosseini; Zahra Borzabadi Farahani; Azam Moslemi; Fatemeh Bodaghi; Fereshteh Farzan Azar (Mashhad University of Medical Sciences, 2023)
Introduction: Dysmenorrhea is a common, painful, and debilitating problem of personal activity with psychological symptoms of anxiety and distress. The present study was performed with aim to investigate the effect of Mandela therapy on anxiety, pain intensity, and distress in primary dysmenorrhea.Methods: This randomized clinical trial study was conducted in 2022 on 80 university students in Arak city who had a pain intensity score of 4 to 8. People were placed in the intervention and control groups. The intervention group painted the mandala for five days in two menstrual cycles. The questionnaires of Spielberger's anxiety, Moos menstrual distress, and numerical pain measure were completed by two groups before and after two intervention periods. Data were analyzed using SPSS statistical software (version 28) and Fisher's exact, independent t and paired t, and Mann-Whitney and Wilcoxon tests. P<0.05 was considered statistically significant.Results: Although the mean score of dysmenorrhea distress after the intervention had a significant decrease in the intervention group (35.76±8.18) compared to the control group (40±7.93) (d=0.645, p=0.01), but the reduction in mean pain intensity in the intervention group (5.82±2.08) was not significantly different compared to the control group (6.45±1.96) (p>0.05). Also, there was no significant difference between the mean of trait and state anxiety in the two groups after the intervention (p>0.05).Conclusion: Mandala therapy can be effective in reducing the distress caused by primary dysmenorrhea.